KEDUDUKAN WANITA SUKU BATAK TOBA YANG MELAKUKAN PERKAWINAN DENGAN PRIA SUKU DILUAR SUKU BATAK TOBA DALAM HUKUM ADAT BATAK TOBA - Meisa, Relinda; Putri, Ririn (PARENTAL, 2014)
AbstractThis research aimed at women of a tribe to know it was toba who performs marriage outside of the tribe was with a guy tribe of toba in customary law was toba as well as a result of the marriage law.This research using research law normative.A kind of law a covering material law the primary and secondary material law.Legal material collected by looking for a study document then analyzed in deductively syllogism. A woman in the toba batak is aligned with men.Equality in terms of heirship and in performing legal action.In performing mating by male batak, outside of the tribe can inflict gord law.Marriage performed batak not a woman to man batak means she citizenry batak, removing custom because man from the outside cannot be batak continuer offspring batak.Mating with men outside the citizenry batak can eliminate customs batak but not eliminate the family woman with his family.Besides the child marriage is entered in customs tribe of her husband.The child is not entitled to the genera batak existing in her mother.But if the man, given genera hence the genera can be passed on to offspring.In it, heirship no effect because basically women have no inheritance.But also can be granted to a woman in compliance with agreement.Keyword: Notch woman, marriage